Public Governance and Environmental Performance: An International Perspective - Handoyo, Sofik; Fitriyah, Fury Khristianty (Journal of Accounting Auditing and Business, 2019)
Purpose of the study is to examine the relationship of public governance and the national environmental performance. Background of the research is driven by the fact that countries located in the same geographic showed different environmental performance. It is believed that public governance will determine national environmental performance. The higher public governance index, the better national environmental performance will be. The subject of the research is the countries that are listed as world bank member. Objects of the research are public governance and environmental performance. Public governance was represented by variables, namely accountability, political stability, government effectiveness, regulatory quality, and control of corruption. Multiple regression analysis was applied in this research. The results showed that accountability, political stability, regulatory quality, and control of corruption have a positive and significant correlation with the national environmental performance. Meanwhile, variable accountability did not correlate with national environmental performance. Government effectiveness was dropped from the analysis due to there is multicollinearity.